12 What is community? Understanding notions of community in relation to English palliative and end of life care and the Ambitions framework. (14th March 2023) - Borgstrom, Erica; Henry, Claire; St-Ledger, Una; Jordan, Joanne
Abstract : Introduction: The Ambitions for Palliative and End of Life Care: a national framework for local action (2015) was relaunched in England in 2021 for another five years. It seeks to provide ambitions and guiding foundations to improve palliative and end of life care. A mapping survey conducted in 2021/2022 showed that Ambition 6 (Each Community is Prepared to Help) was least likely to be focused on. We sought to therefore explore how people understood the notion of community. Methods: Multi-method study involving: 17 individual online interviews (identified as case studies from the survey data), four online focus groups, and one themed interactive online workshop. Focus groups were based on professional role or interest (e.g. commissioners, public, service managers, healthcare staff) and contained between 2–8 participants; workshop included range of professions. All data was transcribed and coded thematically. Results: Participants felt that it was important Ambition 6 was in the framework as it legitimated a focus on the public in palliative care. Yet, community was widely understood as difficult to conceptualise by participants in the context of palliative and end of life care. Notions of community ranged from organisations, the general public, geographical areas, groups of people (including those less likely to be provided specialist services), and frequently referred to 'others' or a nostalgic past. There were disagreements about who has responsible for enabling communities to be prepared to care. Some participants viewed that community work needs to be prioritised above service provision, whilst others felt this was marginal to their service-focused role. Partnership was viewed as key to successful community engagement. Conclusion: Difficulties in understanding and communicating about 'community' makes it difficult to realise an ambition that each community is prepared to help. Discussions about 'community' can facilitate shared learning and innovation within and beyond palliative care providers.